Endothelial Function Is Impaired in Patients Receiving Antihypertensive Drug Treatment Regardless of Blood Pressure Level: FMD-J Study (Flow-Mediated Dilation Japan). Issue 4 (October 2017) - Maruhashi, Tatsuya; Soga, Junko; Fujimura, Noritaka; Idei, Naomi; Mikami, Shinsuke; Iwamoto, Yumiko; Iwamoto, Akimichi; Kajikawa, Masato; Matsumoto, Takeshi; Oda, Nozomu; Kishimoto, Shinji; Matsui, Shogo; et al.
Abstract : Hypertension is associated with endothelial dysfunction. Blood pressure significantly correlates with endothelial function in antihypertensive drug-naive subjects. The purpose of this study was to determine whether treatment status affects the relationship between blood pressure and endothelial function. We measured flow-mediated vasodilation (FMD) in 2297 subjects, including 1822 antihypertensive drug-naive subjects and 475 treated hypertensive patients. FMD significantly decreased in relation to increase in systolic blood pressure (8.2±3.1% in subjects with systolic blood pressure of <120 mm Hg, 7.5±2.8% for 120–129 mm Hg, 7.1±2.8% for 130–139 mm Hg, and 6.7±2.6% for ≥140 mm Hg; P <0.001). Systolic blood pressure was independently associated with FMD in untreated subjects. In contrast, there was no significant relationship between systolic blood pressure and FMD in treated hypertensive patients (4.6±3.1% in treated hypertensives with systolic blood pressure of <120 mm Hg, 4.8±2.7% for 120–129 mm Hg, 4.9±2.8% for 130–139 mm Hg, and 4.5±2.3% for ≥140 mm Hg; P =0.77). Propensity score matching analysis revealed that the prevalence of endothelial dysfunction defined as FMD of less than the division point for the lowest tertile, and the middle tertile of FMD was significantly higher in treated hypertensive patients than in untreated subjects in all systolic blood pressure categories. Endothelial function assessed by FMD was impaired regardless of the level of blood pressure achieved by antihypertensive drug treatment in hypertensive patients. Abstract : Supplemental Digital Content is available in the text.